Kapasitas Usaha Perempuan Pengolah Hasil Pertanian Berbasis Kedelai dan Faktor Karakteristik Personal yang Mempengaruhinya (Studi Kasus Di Kota Mataram) - Hayati Hayati (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2023)
The purpose of this study is to analyze: The production capacity of women who carry out activities of processing agricultural products made from soybeans and the personal characteristics that influence them in the city of Mataram. Three sub-districts with a total of 6 sub-districts were selected as locations for data collection, namely Sandubaya sub-district (Abian Badan Baru Village area), Sekarbela (Karang Pule and Kekalik Jaya Sub-district areas), and Selaparang (Monjok and Monjok Timur Sub-Districts) considering the large number of processing businesses with raw materials. soya bean. A total of 60 respondents were interviewed using a survey approach to obtain information. The data obtained was then processed using both descriptive and inferential statistics using Pearson's correlation, and different ANOVA testing. The results of data processing indicate that the business capacity of women who carry out production activities of soybean-based agricultural products is included in the very high class, and the factors that are thought to influence women's ability to process soybean-based agricultural products in this study are personal characteristics: non-formal education, length of business, motivation to try, access to information, participation in groups).